2011
DOI: 10.1007/s11357-011-9309-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menopause on adipose tissue clock gene genotype and its relationship with metabolic syndrome in morbidly obese women

Abstract: Menopausal women exhibit a loss of circadian coordination, a process that runs parallel with a redistribution of adipose tissue. However, the specific genetic mechanisms underlying these alterations have not been studied. Thus, the aim of the present study was to determine whether the development of menopause induces an alteration of the genes that control biological rhythms in human subcutaneous (SAT) and visceral AGE (2012) (VAT) adipose tissue, and whether changes in clock gene expression are involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…It also regulates gluconeogenic genes in response to PGC-1α activation and modulates lipoprotein metabolism by phosphorylating PGC-1β (118, 119). Mutations and/or deregulation of Ck1δ and ε are associated with colorectal, pancreatic, prostate, breast, and ovarian cancers (102, 120126), neurodegeneration and sleep disorders (127131), chronic inflammation and aging (132, 133), as well as metabolic syndromes (134, 135). Disruption or deregulation of Ck1δ or ε in mice deregulates circadian homeostasis (136) and increases the risk of mammary carcinogenesis (137) and autoimmune diseases (138).…”
Section: The Circadian Genes In Cancermentioning
confidence: 99%
“…It also regulates gluconeogenic genes in response to PGC-1α activation and modulates lipoprotein metabolism by phosphorylating PGC-1β (118, 119). Mutations and/or deregulation of Ck1δ and ε are associated with colorectal, pancreatic, prostate, breast, and ovarian cancers (102, 120126), neurodegeneration and sleep disorders (127131), chronic inflammation and aging (132, 133), as well as metabolic syndromes (134, 135). Disruption or deregulation of Ck1δ or ε in mice deregulates circadian homeostasis (136) and increases the risk of mammary carcinogenesis (137) and autoimmune diseases (138).…”
Section: The Circadian Genes In Cancermentioning
confidence: 99%
“…An additional interesting possibility arises from the demonstration that expression of autophagy genes exhibits a strong diurnal rhythm and may be regulated by biological clock genes [33,34]. Given the increasingly appreciated role of disrupted biological clocks in metabolic diseases [35,36] and early reports that clock genes may be altered in AT in obesity [37,38], it is tempting to propose disturbed clock gene regulation as a putative cause of, or at least a significant contributor to, altered autophagy in AT. In addition, in many obese individuals AT becomes insulin-resistant.…”
Section: Causes Of Increased Adipose Tissue Autophagy In Obesitymentioning
confidence: 99%
“…In experimental studies, it was reported that disruption of the core clockwork by mutations in PER2 increases the susceptibility of mice to spontaneous and irradiation-induced tumors (7). PER2 disruption has also been related to different MetS components, such as abdominal obesity (8,9) and glucose metabolism, via influence on the glucose-6-phosphatase gene (10). Indeed, PER2 2/2 mice have a defective feeding rhythm, are hyperphagic and develop obesity when fed a high-fat diet (11), and have altered blood glucose homeostasis (12), demonstrating the striking influence of diet on this gene.…”
Section: Introductionmentioning
confidence: 99%